PENINGKATAN AKTIVITAS PEMBELAJARAN MELALUI METODE EKSPERIMEN PELAJARAN IPA KELAS IV SDN 05 SUNGAI RAYA - F34209468, kaltumi; ., ngatiyo; ., aunurrahman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: Increased Activity Learning In Material Properties of Liquids Through Experimentation Methods In Natural Science Subjects in the fourth grade Elementary School 05 River Kingdom. This study aims to provide accurate information about the experimental method that can improve student learning activity in learning science in the material properties of the liquid in the class IV SDN 05 River Kingdom. Research methods using experimental learning methods applied through the draft Classroom Action Research (CAR). Through the experiment method can enhance science learning activities in class IV SDN 05 River Kingdom. The increase can be seen from the first cycle of 72%, and the second cycle by 94%. So there is an increase in student learning activities from cycle I to cycle II by 22%. While the learning outcomes of students starting at pre-cycle, the first cycle of 3.58 and 3.88 for the second cycle. So there is an increase in student learning outcomes from the first cycle to the second cycle of 0.30%. Keywords: learning activities, learning science, experimental methods Abstrak: Peningkatan Aktivitas Pembelajaran Pada Materi Sifat-Sifat Benda Cair Melalui Metode Eksperimen Pada Mata Pelajaran Ilmu Pengetahuan Alam di kelas IV Sekolah Dasar Negeri 05 Sungai Raya. Penelitian ini bertujuan untuk memberikan informasi yang akurat tentang metode eksperimen sehingga mampu meningkatkan aktifitas belajar siswa dalam pembelajaran IPA pada materi sifat-sifat benda cair di kelas IV SDN 05 Sungai Raya. Metode penelitian menggunakan metode pembelajaran eksperimen yang diterapkan melalui rancangan Penelitian Tindakan Kelas (PTK). Melalui Metode Eksperimen dapat meningkatkan aktivitas belajar IPA Kelas IV SDN 05 Sungai Raya. Peningkatan dapat dilihat dari siklus I sebesar 72%, dan siklus II sebesar 94%. Jadi ada peningkatan aktivitas belajar siswa dari siklus I ke siklus II sebesar 22%. Sedangkan hasil belajar siswa dimulai dari pra siklus sebesar , siklus I sebesar 3,58 dan siklus II sebesar 3,88. Jadi ada peningkatan hasil belajar siswa dari siklus I ke siklus II sebesar 0,30%. Kata Kunci: aktivitas belajar, pembelajaran IPA, metode eksperimen